Technological Challenges and Opportunities in Trilingual Pedagogy in Teaching Grade 10 Dramatic Arts: Insights from Educators Using Nearpod - Sincuba, Limkani (Digital Technologies Research and Applications, 2026)
Languages can be intertwined in the dramatic arts. Language is a vital human tool for communication. The study explored the challenges and opportunities of trilingual pedagogy, which bridges English, isiXhosa, and isiZulu, in Grade 10 dramatic arts education through Nearpod. By employing a mixed-methods approach, qualitative through a case study of one school and quantitative through a survey of the same school, this investigation provides rich insights into the experiences and perspectives of three educators and eighteen students, as captured through comprehensive focus group interviews. The study aims to uncover both the hurdles and the prospects of implementing multilingual teaching strategies in the dramatic arts. The study was grounded in an interpretive paradigm and underpinned by Vygotsky’s theory. The research highlights Nearpod's role in coordinating multilingual instruction, including scaffolded activities, virtual rehearsals, and real-time polls for language switching during dramatic exercises. Data collection was carried out through focus group interviews and a survey. The collected responses were analysed using ATLAS.ti and thematically. The analysis facilitated the identification and extraction of key themes from participants’ insights. Study findings revealed that challenges included developing trilingual resources and ensuring device access. The study concluded that proactive, collaborative strategies can help educators leverage trilingualism. To utilise trilingual pedagogy on Nearpod, recommendations include teacher training on platform features like Matching Pairs for vocabulary and Time to Climb gamification. The study recommends funding for multilingual content creation and devices. Collaboration among curriculum developers and educators is critical. By proactively leveraging Nearpod, educators could transform trilingual dramatic arts education.